2020
DOI: 10.1097/bot.0000000000001851
|View full text |Cite
|
Sign up to set email alerts
|

Development and Internal Validation of a Prediction Model for In-Hospital Mortality in Geriatric Patients With a Hip Fracture

Abstract: Objective: To develop and validate a prediction model for in-hospital mortality in patients with hip fracture 85 years of age or older undergoing surgery. Design: A multicenter prospective cohort study. Setting: Six Dutch trauma centers, level 2 and 3. Participants: Patients with hip fracture 85 years of age or older undergoing surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…[10][11][12] Numerous prognostic models have been developed for mortality prediction in hip fracture patients, and new models are proposed every year. 11,[34][35][36][37][38] The NHFS is the most studied model and demonstrated adequate discrimination for 30day and 1-year mortality in different studies, although recalibration has occasionally been necessary. 12,16,23,25,39 Despite multiple validation studies, there are no reports on its calibration slope nor clinical usefulness, leaving underfitting or lack of sensitivity potentially underreported.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Numerous prognostic models have been developed for mortality prediction in hip fracture patients, and new models are proposed every year. 11,[34][35][36][37][38] The NHFS is the most studied model and demonstrated adequate discrimination for 30day and 1-year mortality in different studies, although recalibration has occasionally been necessary. 12,16,23,25,39 Despite multiple validation studies, there are no reports on its calibration slope nor clinical usefulness, leaving underfitting or lack of sensitivity potentially underreported.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to validate a previously developed prediction model (U-HIP) for in-hospital mortality in geriatric hip fracture patients [8] . In this large retrospective cohort study using NSQIP data, the model showed a fairly good predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome for this study was in-hospital mortality. In this study, the authors decided to validate the model in patients aged 70 years or above, even though the development cohort consisted of patients 85 year or above [8] . The cut-off of 70 years was chosen because the vast majority of patients who experience inhospital mortality after a hip fracture are aged 70 years or above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations